Price Formation on Land Market Auctions in East Germany - An Empirical Analysis - Silke Huẗtel; Martin Odening; Karin Kataria; Alfons Balmann (German Journal of Agricultural Economics (GJAE), 2013)
Although determinants of agricultural land prices have received considerable attention in the literature, little is known about price formation on structured markets such as land auctions. This paper aims to empirically test theoretical predictions regarding price formation in land market auctions. The analysis is conducted for the case of Saxony-Anhalt, Germany, where state-owned land constitutes a significant share of the agricultural land market. The utilised data consists of public auction data provided by the Land-gesellschaft Sachsen-Anhalt (i.e. the rural development agency in Saxony-Anhalt), and covers approximately 700 calls for bids from 2003 to 2010, supplemented with regional and structural data. Spatial correlation of land prices is considered by applying a spatial econometrics approach. Our analysis shows that apart from land characteristics, the number of bidders and the share of non-agricultural investors have an impact on the land price.
Keywords: 330; Auktion; Immobilienpreis; Landwirtschaftliche Immobilien; Sachsen-Anhalt